An analysis of causes of default risk and its impact on Micro-Financial Institution’s performance : A case of SMEDCO - Machaka, Chipo E (Midlands State University, 2020)
The study focused on the analysis of the causes of default risk and its impact on the performance of MFI’s. SMEDCO was used as the case of study. The main objective of the study was to identify the main causes of default risk and to assess its impact on the performance of MFIs. Descriptive research was used for the study since there was a case of SMEDCO to enhance the study. The population of the study was 46, and 35 of 46 were set aside as the target population. Random and purposive sampling methods were used to come up with the sample size which was 25. The study applied the combined approach which takes into account both qualitative and quantitative information. Primary data was collected through the use of questionnaires which were given to SMEDCO employees at 170 Chinhoyi Street, Harare to fill and face to face interviews were carried out with some who were randomly selected from the sample. Data was presented through the use of tables, graphs, and pie charts and was analyzed using the reference of other authors who conducted the same studies and had similar or different results. The results indicated that the rate default risk was very high as well as the rate of losses as from 2008 up to 2016. The study then concluded that there was much to be done to reduce the levels of default risk in order to reduce losses, and it recommended that there should be high frequent repayment periods, a sharpened assessment process before issuing of loans and a critical credit analysis of clients before disbursement to reduce default risk.